Changes in psychological and relationship dimensions of sexuality after trauma focused therapy in women with interpersonal child abuse related PTSD - Weiß, Judith; Bornefeld-Ettmann, Pia; Kleindienst, Nikolaus; Müller-Engelmann, Meike; Priebe, Kathlen; Steil, Regina (Journal of trauma & dissociation, 2025)
Women with posttraumatic stress disorder (PTSD) often report problems with sexuality. Relationship dimensions and psychological dimensions of sexuality seem to be impaired. We examined whether trauma focused therapies improve relationship and psychological dimensions of sexuality. In a randomized controlled trial that took part between 2014 and 2016 in Germany, N = 193 cisgender women with PTSD after child abuse (mean age = 36.3 years) completed the Multidimensional Sexuality Questionnaire, assessing psychological dimensions of sexuality and the Resources in Sexuality and Partnership, assessing relationship dimensions of sexuality. PTSD was assessed via Clinician Administered PTSD Scale for DSM-5. Assessments took part in the beginning and after Dialectical Behavior Therapy for PTSD or Cognitive Processing Therapy. Using hierarchical linear modeling, changes in psychological and relationship dimensions of sexuality from beginning to post treatment were assessed, also the association between PTSD symptom reduction and reduction in psychological and relationship dimensions. From beginning to post treatment, relationship dimensions of sexuality improved (p < .01; Cohen’s d = .36). PTSD symptom reduction moderated this effect. The psychological dimension sexual satisfaction increased (p < .05; Cohen’s d = .32), sexual anxiety (p < .001; Cohen’s d = ‒.51) and sexual depression (p < .001; Cohen’s d = ‒.44) decreased. PTSD symptom reduction moderated these effects. Sexual esteem and sexual motivation did not change after therapy. Our results suggest that relationship dimensions and some psychological dimensions of sexuality can improve after trauma focused therapy. Other psychological dimensions like sexual esteem might need specific therapeutic interventions to improve.